ON THE RELATIONSHIP BETWEEN LISTENING COMPREHENSION MOTIVATION AND LISTENING COMPREHENSION AMONG THE IRANIAN EFL LEARNERS - Seyed Mohammad Jafari (Indonesian JELT, 2010)
The present study was undertaken to investigate the relationship between Iranian EFL learners’ listening comprehension (LC) and their English listening comprehension motivation (ELCM). It was also aimed at determining the role of gender and years of university study in LC and ELCM. Sixty four Iranian EFL students (32 males and 32 females), majoring in Teaching English as a Foreign Language at the Marvdasht Azad University participated in this study. They included freshmen, sophomores, juniors, and seniors.Participants' listening comprehension motivation was measured by English listening comprehension motivation scale (ELCMS) developed by Hsu from Chang's Intrinsic Motivation Orientation Scale (2001). A portion of TOEFL test of language proficiency constructed by the Educational Testing Service (ETS, 2001) was used to determine listening comprehension proficiency level of the participants. The results revealed that the relationship between ELCM and LC was positive and significant. That is, the higher the level of ELCM of the students, the higher the score they attained on the LC test and vice versa. This result indicates that ELCM enhances foreign language listening.An analysis of variance (ANOVA) revealed that the years of university study contributed to the level of listening proficiency. That is, the level of LC proficiency increased as a function of years of university study. Concerning the relationship between ELCM and years of university study, no correlation was found. In addition, in this study the data showed no significant difference between males and females’ listening comprehension motivation scores. Keywords:      Listening comprehension (LC), English listening comprehension motivation (LCM), L2 listeners, English as a foreign language (EFL), motivation.